Komi can't communicate. Volume 17 - Oda, Tomohito, 1991-; Werry, John (Translator) (VIZ Media, LLC, 2022)
Socially anxious high school student Shoko Komi's greatest dream is to make some friends, but everyone at school mistakes her crippling social anxiety for cool reserve! Luckily she meets Tadano, a timid wallflower who decides to step out of his comfort zone in order to help her achieve her goal of making 100 friends. The Itan High culture festival is supposed to be a fun time for all, but Rumiko Manbagi's enjoyment is ruined when she comes to an awful realization--she and Komi are rivals for Tadano's love! Can her friendships with Komi and Tadano survive this crushing complication?